Oral bioavailability enhancement of doxazosin mesylate: Nanosuspension versus self-nanoemulsifying drug delivery systems - Al Zahraa G. Al Ashmawy; Mohammad H. Alyami; Noura G. Eissa; Gehan F. Balata; Hanan M. El Nahas (International Association of Physical Chemists (IAPC), 2023)
Background and purpose: Doxazosin mesylate (DOX) is an antihypertensive drug that possesses poor water solubility and, hence, poor release properties. Both nanosuspensions and self-nanoemulsifying drug delivery systems (SNEDDS) are becoming nanotechnology techniques for the enhancement of water solubility of different drugs. Experimental approach: The study's goal was to identify the best drug delivery system able to enhance the release and antihypertensive effect of DOX by comparing the physical characteristics such as particle size, zeta potential, entrapment efficiency, release rate, and main arterial blood pressure of DOX-loaded nanosuspensions and SNEDDS in liquid and solid form. Key results: DOX nanosuspension preparation had a particle size of 385±13 nm, poly-dispersity index of 0.049±3, zeta potential of 50 ± 4 mV and drug release after 20 min (91±0.43 %). Liquid SNEDDS had a droplet size of 224±15 nm, poly-dispersity index of (0.470±0.01), zeta potential of -5±0.10 mV and DR20min of 93±4 %. Solid SEDDS showed particle size of 79±14 nm, poly-dispersity index of 1±0.00, a zeta potential of -18 ±0.26 mv and DR20min of 100 ±2.72 %. Conclusion: Finally, in terms of the mean arterial blood pressure lowering, solid SNEDDS performed better effect than both liquid SNEDDS and nanosuspension (P >0.05).